A collaborative navigation method based on partnership optimisation for clustered aircraft. Issue 6 (26th February 2022) - Wang, Rong; Chen, Xin; Xiong, Zhi; Zhang, Huiyuan; Liu, Jianye
Abstract: The collaborative exchange of information between members of a cluster can provide additional observations to improve the reliability of navigation. To address the problems of poor geometric configurations of satellites and low positioning accuracy of satellite navigation systems in complex environments, this paper proposes a collaboration‐augmented navigation method with optimisation of the geometric dilution of precision for a clustered aircraft. A collaboration‐augmented navigation model is established in which the differences between the characteristics of satellite pseudorange measurements and collaborative information measurements are taken into consideration to overcome heteroscedasticity. Then, an optimal collaboration‐augmented navigation algorithm is proposed on the basis of geometric configuration analysis. In this method, all visible satellites are projected onto the current horizontal plane, and in accordance with the satellite distribution, a satellite reference ring is constructed to determine the optimal collaborative area for an aircraft. Then, a collaborative aircraft selection is made to select an optimal aircraft to assist the satellite navigation system for configuration optimisation. Finally, the algorithm performance is simulated and verified by simulation, and the influence of the equivalent ranging error on the effectiveness of geometric configuration optimisation is analysed, indicating the effectiveness of the proposed method.